Analisis Situasi Penyakit Menular di Kabupaten Bogor Tahun 2024 Menggunakan Metode Paho-Adapted Hanlon - Muhammad Nur Muslim Shidiq; Tri Yunis Miko Wahyono; Adang Mulyana (Jurnal Ners, 2026)
Bogor Regency is part of West Java Province that has experienced an increase in infectious disease cases. The purpose of this situational analysis is to obtain an overview and prioritize the issues of infectious diseases in Bogor Regency in 2024. The research was conducted from October 2024 to December 2024. The determination of problem priorities uses the PAHO-adapted Hanlon method with assessment indicators, namely Magnitude (A), Seriousness of the Problem (B), Urgency (B1), Severity of Consequences (B2), Economic Loss (B3), Negative Impact on Others (B4), Effectiveness of Interventions (C), Inequity (E), and Institutional Factor (F) thru interviews with relevant parties in the Bogor District Health Office. The ranking of problem priorities based on the PAHO score results is presented in the order (A, B, B1, B2, B3, B4, C, E, F, Total). The priority issue of infectious diseases in Bogor Regency is HIV/AIDS with a score of (7.75; 3.83; 3.92; 4.00; 4.08; 5.33; 3.08; 1.11; 32.37). The need to strengthen cross-sector collaboration, between the government and the private sector, to expand the reach of education, facilitate economic empowerment for affected populations, and eliminate stigma and discrimination across all layers of society in Bogor Regency. Keywords: Situation Analysis, HIV, PAHO, Infectious Diseases